Potency of Medicinal Plants for Eradication of Avian Influenza : In Vitro Test on Vero Cells - Agus Setiyono; Nurliani Bermawie (Jurnal Sain Veteriner, 2013)
Some of medicinal plants indicate their potency as anti-viral such as Sambiloto (Andrographis paniculata Nees), Temu Ireng (Curcuma aeruginosa L.), Beluntas (Pluchea indica L.) Sirih Merah (Piper crocatum) and Adas (Foeniculum vulgare).  Avian Influenza (AI) H5N1 strain viruses used in this study was isolated from field in Cikole area, West Java in July 20th 2007.  To explore the potency of medicinal plants as anti-viral substance, the consecutive assays were performed by virus infection inhibition test in in vitro study using Vero cells.  After the Vero cells were growing confluently, they were treated with sterilized-extract of medicinal plants either in single or combination.  Furthermore, the culture cells were infected with AI H5N1 strain virus, then incubated at 37oC and examined for cytopathic effect (CPE) microscopically.  The result showed that extract of Sambiloto and combination of Sambiloto and Temu Ireng were stronger than others in inhibition of virus attachment and infection to the cells.  The Vero cells still alive up to 3rd day post infection with AI H5N1 virus after treatment with Sambiloto and Temu Ireng.  In conclusion, extract of Sambiloto and Temu Ireng showed their potency as candidate for anti-viral substances that may needed for eradicating AI infection.